Introduction of Financial Institutions (Islamic Banks and Islamic Financial Institutions) To Students Of Integrated Islamic High School At-Tibyan Banyuasin - Heri Junaidi; Nilawati; Mismiwati; Citra Etika; Amrina Rosyada (CV. Doki Course and Training, 2023)
ABSTRACT Financial institutions are an example of how Islamic economics is used, which forbids the use of interest or usury systems in the economy since they are seen as usury, which is against religious law. This is particularly true of the banking industry. However, a lot of people are still unaware of Indonesian Islamic banking, particularly among schoolchildren. Students at At-Tibyan Integrated Islamic High School appear to exhibit this phenomena as well. Some of them are completely unaware of the existence of Islamic banks, while others do not even have a basic understanding of financial organizations. This activity aims to educate students at At-Tibyan Integrated Islamic High School about financial institutions, namely Islamic banks and Islamic financial institutions, and to enhance their ability to apply the theory and information they have learned. The approach used in this socialization exercise is closely related to the community education (popular education) approach, which entails service projects meant to enhance the community's resources and capacities or to learn alongside it. This approach to community education involves the active participation of all participants in the training process and is structured around a pattern of explicit instruction, direct teaching, and question and answer sessions. It is supplemented by a simulation method that involves direct practice with material related to financial institutions. Students at At-Tibyan Integrated Islamic High School are projected to have an influence on the future expansion of the Sharia financial industry as a result of this socialization program, which has increased their awareness of conventional financial institutions.